Q: Factorization of x2 plus 12x plus 27?

Write your answer...

x2+12x+28Improved Answer:--x2+12x+28 = (-x+14)(x+2) when factored

x + 12x + 20 = (x + 10)(x + 2)

-((x + 2)(x - 14))

3x(x2 + 2x - 4)

-((x + 2)(x - 14))

3x(x2 + 2x - 4)

-2x3 + 2x2 + 12x =(-2x) (x2 - x - 6) =(-2x) (x+2) (x-3)

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

x2-12x+36 = (x-6)2

x2 + 12x + 32 = (x + 8)(x + 4)

x2 + 12x + 32 = (x + 4)(x + 8)

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

3x3+12x = 3x(x2+4)

-(x - 14)(x + 2)

-2x3 + 2x2 + 12x = -2x(x2 - x - 6) = -2x(x2 + 2x - 3x - 6) = -2x[ x(x + 2) - 3(x + 2) ] = -2x(x - 3)(x + 2)

x^2 - 12x + 27 You're looking for factors of 27 that will combine to make 12. (x - 3)(x - 9)

x2-12x+35 = (x-5)(x-7)

x2 + 12x - 11 = x2 + 12x + (12/2)2 - (12/2)2 - 11 = (x + 6)2 - 47

3x2 + 36x + 81 = 3(x2 + 13x + 27)

x(x + 4)(x - 3)

-2x3 - 2x2 + 12x = -2x(x2 + x - 6) = -2x(x2 - 2x + 3x - 6) = -2x[ x(x - 2) + 3(x - 2) ] = -2x(x + 3)(x - 2)

168

If you mean: x^2 +12x +20 then it is (x+2)(x+10) when factored

x2+12x+36=0 2x+12x+36=0 14x+36=0 14x=-36 x=-36/14 x=-2 4/7

(x + 7)(x + 5)